2019
DOI: 10.1094/pdis-11-18-1976-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Phytophthora cinnamomi in American Chestnut (Castanea dentata) Backcross Populations that Descended from Two Chinese Chestnut (Castanea mollissima) Sources of Resistance

Abstract: Restoration of American chestnut (Castanea dentata) depends on combining resistance to both the chestnut blight fungus (Cryphonectria parasitica) and Phytophthora cinnamomi, which causes Phytophthora root rot, in a diverse population of C. dentata. Over a 14-year period (2004 to 2017), survival and root health of American chestnut backcross seedlings after inoculation with P. cinnamomi were compared among 28 BC3, 66 BC4, and 389 BC3F3 families that descended from two BC1 trees (Clapper and Graves) with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In order to identify important structural and functional elements of genomes and use valuable genetic variation for breeding, accurate, complete and contiguous genome assemblies are essential (Love et al 2014). Previous studies have shown that combining Pacific Biosciences (PacBio) and Illumina data significantly improve N50 length and generate more accurate assemblies (Koren et al 2012;Jiao et al 2017;Westbrook et al 2019). High-throughput chromosome conformation capture (Hi-C) is a cost-effective technique for assigning, ordering, and orienting genomic sequences onto chromosomes (Lin et al 2018).…”
mentioning
confidence: 99%
“…In order to identify important structural and functional elements of genomes and use valuable genetic variation for breeding, accurate, complete and contiguous genome assemblies are essential (Love et al 2014). Previous studies have shown that combining Pacific Biosciences (PacBio) and Illumina data significantly improve N50 length and generate more accurate assemblies (Koren et al 2012;Jiao et al 2017;Westbrook et al 2019). High-throughput chromosome conformation capture (Hi-C) is a cost-effective technique for assigning, ordering, and orienting genomic sequences onto chromosomes (Lin et al 2018).…”
mentioning
confidence: 99%
“…Borkh.) approached 100 and 90 percent mortality, respectively, during the same time period when challenged with the same inoculum (23ss04) using the same inoculation methods, and under similar environmental conditions [12,17,18]. Furthermore, in a similar resistance screening of 32 Abies species, only the single most resistant species demonstrated less mortality than Eastern white pine [11].…”
Section: Discussionmentioning
confidence: 84%
“…A large main study was conducted using a standard culture of P. cinnamomi, 23ss04, isolated from Fraser fir and employed in several published studies involving fir (Abies) and chestnut (Castanea) species [11,12,17,18]. For comparison, a smaller supplemental study was conducted using isolate 2334 from Eastern white pine.…”
Section: Inoculum Production and Inoculationmentioning
confidence: 99%
“…Furthermore, American chestnuts from across the species range are highly susceptible to Phytophthora cinnamomi (the oomycete responsible for Phytophthora root rot) - a contemporary agent of American chestnut decline (69, 70). To date, the only known source of P. cinnamomi resistance for C. dentata has been introgression from Asian Castanea species, such as C. mollissima and C. crenata (7072). Thus, the enrichment for defense genes among selection targets we observed is unlikely to be related to these two contemporary pathogens that threaten the species.…”
Section: Discussionmentioning
confidence: 99%